2014
DOI: 10.1371/journal.pone.0102784
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear DNA Perspective on Delineating Evolutionarily Significant Lineages in Polyploids: The Case of the Endangered Shortnose Sturgeon (Acipenser brevirostrum)

Abstract: The shortnose sturgeon, Acipenser brevirostrum, oft considered a phylogenetic relic, is listed as an “endangered species threatened with extinction” in the US and “Vulnerable” on the IUCN Red List. Effective conservation of A. brevirostrum depends on understanding its diversity and evolutionary processes, yet challenges associated with the polyploid nature of its nuclear genome have heretofore limited population genetic analysis to maternally inherited haploid characters. We developed a suite of polysomic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…After extensive sampling and work with commercial fishermen, they captured 2 shortnose sturgeon. Both fish were gravid females, and telemetric and recapture data indicated that one fish spawned in the Potomac River (Kynard et al, 2009). As with the genetic samples collected during the Chesapeake Bay reward program, the 2 gravid females could not be genetically differentiated from Delaware River shortnose sturgeon (King et al, 2014).…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…After extensive sampling and work with commercial fishermen, they captured 2 shortnose sturgeon. Both fish were gravid females, and telemetric and recapture data indicated that one fish spawned in the Potomac River (Kynard et al, 2009). As with the genetic samples collected during the Chesapeake Bay reward program, the 2 gravid females could not be genetically differentiated from Delaware River shortnose sturgeon (King et al, 2014).…”
mentioning
confidence: 88%
“…The shortnose sturgeon (Acipenser brevirostrum) is an amphidromous sturgeon reported to inhabit the continental slope of the Atlantic Ocean from New Brunswick, Canada, to Florida (Gruchy and Parker, 1980;Dadswell et al, 1984;Kynard, 1997). However, Dadswell et al (2013) documented a single shortnose sturgeon captured in a weir in the Minas Basin, an inlet of the Bay of Fundy in Nova Scotia, Canada, and that capture represents a modest extension of the northern range for this species.…”
mentioning
confidence: 99%
See 3 more Smart Citations